If this is true, what does it imply? How end-user antibody validation facilitates insights into biology and disease - Karen S. Sfanos; Srinivasan Yegnasubramanian; William G. Nelson; Tamara L. Lotan; Ibrahim Kulac; Jessica L. Hicks; Qizhi Zheng; Charles J. Bieberich; Michael C. Haffner; Angelo M. De Marzo (Asian Journal of Urology)
Antibodies are employed ubiquitously in biomedical sciences, including for diagnostics and therapeutics. One of the most important uses is for immunohistochemical (IHC) staining, a process that has been improving and evolving over decades. IHC is useful when properly employed, yet misuse of the method is widespread and contributes to the “reproducibility crisis” in science. We report some of the common problems encountered with IHC assays, and direct readers to a wealth of literature documenting and providing some solutions to this problem. We also describe a series of vignettes that include our approach to analytical validation of antibodies and IHC assays that have facilitated a number of biological insights into prostate cancer and the refutation of a controversial association of a viral etiology in gliomas. We postulate that a great deal of the problem with lack of accuracy in IHC assays stems from the lack of awareness by researchers for the critical necessity for end-users to validate IHC antibodies and assays in their laboratories, regardless of manufacturer claims or past publications. We suggest that one reason for the pervasive lack of end-user validation for research antibodies is that researchers fail to realize that there are two general classes of antibodies employed in IHC. First, there are antibodies that are “clinical grade” reagents used by pathologists to help render diagnoses that influence patient treatment. Such diagnostic antibodies, which tend to be highly validated prior to clinical implementation, are in the vast minority (e.g. < 500). The other main class of antibodies are “research grade” antibodies (now numbering >3 800 000), which are often not extensively validated prior to commercialization. Given increased awareness of the problem, both the United States, National Institutes of Health and some journals are requiring investigators to provide evidence of specificity of their antibody-based assays. Keywords: Prostate cancer, Antibodies, Immunohistochemistry